Leverage Strategies of Asian REITs and Real Estate Operating Companies - LIM, Kian Guan (Institutional Knowledge at Singapore Management University, 2014)
The real estate literature has been puzzled by the story of why a tax-exempt vehicle like REITs uses more debt than equity. We used empirical evidence on REITs and real estate operating companies (REOCs) in Japan, Singapore, and Hong Kong from 2006 to 2010 and verified that REITs did use more debt than REOCs, despite borrowing constraints imposed on REITs in Hong Kong and Singapore. REITs also used more short-term debt to finance their real estate investment activities, but their total debt level declined during the crisis periods in 2007 and 2008. We found that higher long-term debt reduced the price over net asset value ratio (P/NAV), while short-term debt increased P/NAV of the real estate firms during normal times. However, the leverage effects of both the long-term and short-term debts were reversed when the credit crunch occurred in 2007 and 2008. Our study provides a better understanding of how REITs in Asia strategically employ larger amounts of short-term debt funding during normal times due to the lower funding cost, and not for tax or signaling reasons. However, during a financial credit crunch, REITs that do not substitute short-term debt by long-term debt are exposed to huge refinancing risks and their stock prices are heavily discounted. The results are in line with a strategic pecking order of first using cheap short-term funding and reversing into equity funding when debt cost rises. Our results do not support the tax and signaling effect, but are consistent with the clientele effect.